Alternative potency tests for quality control of immunobiologicals: a critical review of the validation approach - Wildeberg Cal Moreira; Nathalia de Souza Machado; Jéssica Ferreira de Souza Freitas; Antônio Eugênio Castro Cardoso de Almeida; Wlamir Correa de Moura (Fundação Oswaldo Cruz (FIOCRUZ), 2020)
Introduction: In addition to low reproducibility, in vivo potency tests used in the quality control of immunobiological products require too many animals, causing them significant pain and suffering. In the last decades, many studies have been conducted to validate alternative methods for quality control and batch release of products such as vaccines and other immunobiologicals, especially for potency tests. Objective: To discuss validation studies on alternative methods proposed for replacing the in vivo potency tests and the used statistical approach, as well as to propose harmonization of terminology and to design validation studies for alternative potency methods. Method: A review of scientific databases was carried out to compile the products, data on the validation procedures and to verify their inclusion in the pharmacopeias. Results: Four trials were incorporated into the pharmacopeias. Statistical approaches included mainly regression assessment, ANOVA and Chi-square test. Conclusions: It is a challenge to conduct appropriate validation studies that are widely accepted by regulatory authorities, especially where validation centers have not yet been established. A clear indicator of this difficulty was the low number of methods for biological products incorporated into the guidelines.